1992
DOI: 10.1111/j.1365-2559.1992.tb00338.x
|View full text |Cite
|
Sign up to set email alerts
|

Pseudoangiosarcomatous carcinoma: a clinicopathological study of seven cases

Abstract: Seven cases of carcinoma mimicking angiosarcoma occurring in skin (3 cases), breast (3) and lung (1) are described. The cutaneous, pulmonary and one of the breast carcinomas were poorly differentiated and squamous in type; the other two breast tumours were poorly differentiated ductal carcinomas with focal squamous differentiation. Histologically, the pseudoangiosarcomatous pattern was due to complex anastomosing channels and spaces lined by neoplastic cells. The spaces contained hyaluronic acid. The neoplasti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
52
1
1

Year Published

1999
1999
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(56 citation statements)
references
References 39 publications
2
52
1
1
Order By: Relevance
“…Except in the lip (perhaps due to early detection and treatment), the head and neck mucosal ASCCs reported were associated with poor prognoses. Histomorphologically, ASCC may lose the typical features of SCC and mimic other epithelial or mesenchymal malignancies because of advanced acantholysis and dyskeratosis [5,11,12]. Because of its rarity, most of the previous studies have been case reposts and information concerning the immunohistochemical features of ASCC is limited.…”
Section: Introductionmentioning
confidence: 99%
“…Except in the lip (perhaps due to early detection and treatment), the head and neck mucosal ASCCs reported were associated with poor prognoses. Histomorphologically, ASCC may lose the typical features of SCC and mimic other epithelial or mesenchymal malignancies because of advanced acantholysis and dyskeratosis [5,11,12]. Because of its rarity, most of the previous studies have been case reposts and information concerning the immunohistochemical features of ASCC is limited.…”
Section: Introductionmentioning
confidence: 99%
“…1,2,10 The few ASCC cases that have been reported in the veterinary literature are divided into pseudoglandular and acinar variants. 4,5,12 To the authors' knowledge, the PASCC variant has not been reported previously in the veterinary literature.…”
mentioning
confidence: 99%
“…5 The human entity is characterized by anastomosing cords of epithelioid cells, with multiple vascular clefts formed within the neoplastic nodules. 1,2,6,10,13,15 The vascular clefts are believed to be caused by acantholysis of the neoplastic cells that occurs at the center of the neoplastic cords, with subsequent infiltration of these clefts by erythrocytes. Decreased expression of intercellular adhesion molecules, such as E-cadherin and syndecan-1, results in decreased adhesion of epithelial cells, which eventually leads to acantholysis.…”
mentioning
confidence: 99%
“…In the breast, pure squamous cell carcinoma is rare, although approximately 4% of invasive ductal carcinomas show foci of squamous cell metaplasia [7]. Over the last 20 years, only seven cases of primary ASCC of the breast have been reported [2,6,16]. However, Eusebi et al [6] reviewed the older case series by Gersell and Katzenstein [8] and Toikkanen [20] and pointed out that, based on their histological description, probably several of their cases showed acantholytic features.…”
Section: Discussionmentioning
confidence: 99%